The effectiveness of Kampung Tanpa Wayar (KTW) program on community satisfaction / Mohd Zulfikar Zaili and Rexmision Mike Napis - Zaili, Mohd Zulfikar; Napis, Rexmision Mike (2016)
The purpose of this study is to identify the effectiveness of Kampung Tanpa Wayar (KTW) program on community satisfaction in Kampung Barn, Tatau. The main research objective of the study was to find out the most influence factors that affect the level ofsatisfaction ofthe community. The method that the researchers use to collect all of data and information is by using the questionnaire. The target size of the study is 248 respondents from 734 numbers of communities in Kampung Baru, Tatau. The researchers have used convenience sampling technique to select the respondents as it was accessibility and quickness to get the information. Three hypotheses are using in the study in order to identified the influence factors, level of satisfaction and the effects towards the community. From the study, it showed that the level of satisfaction ofthe community that using the KTW program are not high as the influence factors affect their satisfaction. Besides, the effects of KTW program towards the community showed the average result.